Happiness Surveys and Public Policy: What’s the Use? - Adler, Matthew D. (2013)
Cost-benefit analysis (CBA) is the primary tool used by policymakers to inform administrative decisionmaking. Yet its methodology of converting preferences (often hypothetical ones) into dollar figures, then using those dollar figures as proxies for quality of life, creates significant systemic errors. These problems have been lamented by many scholars, and recent calls have gone out from world leaders and prominent economists to find an alternative analytical device that would measure quality of life more directly. This Article proposes well-being analysis (WBA) as that alternative. Relying on data from studies in the field of hedonic psychology that track people's actual experience of life—data that have consistently been found reliable and valid—WBA is able to provide the same policy guidance as CBA without CBA's distortionary reliance upon predictions and dollar figures. We show how WBA can be implemented, and we catalog its advantages over CBA. In light of this comparison, we conclude that WBA should assume CBA's role as the decisionmaking tool of choice for administrative regulation